Programme management and compliance: the backbone of a successful Global Mobility Function? - Dickmann, Michael; Piacentini, Andrea (Profile Locations, 2017)
“It is not enough to take good decisions and make good choices. It is necessary to take heed and comply with whatever you plan.” Israelmore Ayivor’s quote perfectly captures the challenges of global mobility (GM) programme management; especially if one factors in the frequently changing legal regulations of governments around the world which, by their nature, increase the complexity that GM departments have to handle. This article investigates the trends in GM programme and compliance management and is based on research amongst RES Forum members in 65 large multinationals across a wide crosssection of industries.